Treatment of primary cutaneous anaplastic large cell lymphoma with superficial X-rays - Malene E. Jepsen; Robert Gniadecki (PAGEPress Publications, 2015)
The optimal radiation schedule for primary cutaneous anaplastic lymphoma (PCALCL) has not been investigated. We report here satisfactory outcomes of low-dose (16-20 Gy, 3-5 fractions), superficial X-ray radiation (40-50 kV) in a series of 10 patients with PCALCL. Only 1 patient developed a local relapse during the median observation time of 25 months; complete remission was recorded in the other patients. This observation indicates that superficial, low dose X-ray therapy may provide a cost-effective alternative to the traditional 35-45 Gy schedules.